Bioplastic From Renewable Resource: Utilization Of Orange Peel Cellulose And Pearl Millet Pectin For Anti-Biofilm Properties —– A Review - K Arungandhi; Sreya Balakrishnan (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
Plastics are widely used everywhere such that in packing of food, substance and also they are harmful for environment. This is because it is versatile, durable and easy to carry. Plastic are non-biodegradable waste and cause pollution for environment. So to resolve the problem we can use bioplastic biodegradable films etc. The development of biodegradable films can decrease its use such a way that now food industries, textile industries, etc. Use biodegradable films as alternative. Biodegradable films are thin, flexible materials that can decompose naturally in the environment, typically within a few months to a few years. The increasing demand for sustainable and eco-friendly materials has led to the exploration of alternative sources for biodegradable films. Orange peel and Pearl millet are two agricultural waste materials that have shown promise in this regard. The isolation of cellulose from orange and pectin from pearl millet. The film is been produced by both cellulose and pectin which is been coated with PVA, its anti-biofilm activity is been tested. Highlights the challenges and future prospects of using these materials in bioplastic. Bioplastic are used in packaging, agriculture, and medicine, providing a sustainable alternative to traditional plastics. Biodegradable films are designed to provide a physical barrier or packaging solution. Thereby material can be recycled and reuse to make it innovative, and production of plastic will be reduced and pollution will be decreased.